A short profile of the Greater Region and the Upper Rhine region - Andrea Hartz; Beate Caesar (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
The institutionalisation of border regions has a long history. Initial forms of cooperation usually emerged in relation to a specific event. The 1970s were decisive for the emergence of cross-border organisations in both the Greater Region and the Upper Rhine region. Over the decades the structures were consolidated, although regionally specific adaptations and developments continue both on a conceptual and practical level. The European INTERREG A programme has played a significant role in improving cross-border cooperation, and INTERREG continues to be an important factor in the implementation of cross-border projects. Efforts to further develop the institutional framework and cooperation structures in recent years demonstrate that there are still many challenges but also unexploited potential in the Greater Region and the Upper Rhine region.
urn:nbn:de:0156-40970486; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Greater Region; Upper Rhine region; cross-border cooperation; institutionalisation; INTERREG